Development and validation of a fluorescence-based HTS assay for the identification of P/Q-Type calcium channel blockers - Mezler, Mario; Draguhn, Andreas (Combinatorial chemistry & high throughput screening, 2012)
Dysfunction of P/Q-type calcium channels is thought to underlie a variety of neurological diseases. There is evidence that migraine, Alzheimer’s ...